A mathematical investigation of Sol LeWitt's Wall Drawing 413. Issue 4 (2nd October 2022) - Ahlstrom, Lydia
ABSTRACT: This exploration will examine the presence of algebraic and topological structures in the conceptual artist Sol LeWitt's large-scale panel called Wall Drawing 413 . The algebraic structures will focus on group theory found in the permutations of the four colors used and a topological investigation that will classify some of the compact 2-dimensional surfaces that can be constructed from gluing edges of matching colors of one 4 × 4 square in the artwork. GRAPHICAL ABSTRACT: UF0001